Palladium-based pseudohomogeneous catalyst for highly selective aerobic oxidation of benzylic alcohols to aldehydes - Homa Targhan; Aram Rezaei; Alireza Aliabadi; Ali Ramazani; Zhefei Zhao; Huajun Zheng (Scientific Reports, 2024)
Abstract This study presents a novel class of pseudohomogeneous catalysts (PHC) based on carbon quantum dots functionalized with terpyridine ligands (CQDs-Tpy) to immobilize and stabilize palladium nanoparticles (Pd NPs). Extensive characterization techniques clearly confirmed the successful stabilization of Pd NPs on CQDs-Tpy. The effectiveness of the catalyst was demonstrated in the selective aerobic oxidation of primary and secondary of benzylic alcohols to aldehydes in the absence of additives and phase transfer catalyst (PTC). Remarkably, the reactions predominantly yielded aldehydes without further oxidation to carboxylic acids. By employing low catalyst loadings (0.13 mol%), high conversions (up to 89%) and excellent selectivity (> 99%) of the aldehyde derivatives were achieved. Moreover, the CQDs-Tpy/Pd NPs catalyst displayed suitable catalytic activity and recyclability, offering potential economic advantages. This promising approach opens up new opportunities in the field of catalysis for designing subnanometric metal-based PHCs.